A 2-year aeropalynological survey of allergenic pollen in the atmosphere of Kastamonu, Turkey - Ceter, Talip; Pinar, N. M.; Guney, Kerim; Yildiz, Atila; Asci, Baris; Smith, Matt (Springer Science and Business Media LLC, 2011)
Knowledge of airborne pollen concentrations and the weather conditions influencing them is important for air quality forecasters, allergists and allergy sufferers. For this reason, a 7-day recording volumetric spore trap of the Hirst design was used for pollen monitoring between January 2006 and December 2007 in Kastamonu, Turkey. A total of 293,427 pollen grains belonging to 51 taxa were recorded during the study period. In the 2 years of study, the period March–August was identified as the main pollination season for Kastamonu. The highest monthly pollen counts were observed in May in both years. Six taxa made up 86.5% of the total amount of pollen recorded in the atmosphere of Kastamonu. These were as follows: Pinaceae (42.9%), Cupressaceae (20.6%), Poaceae (9.7%), Quercus (5.5%) Betula (5.3%) and Carpinus (2.6%). Four of these are considered to be highly allergenic (Betula, Carpinus, Cupressaceae and Poaceae). There were also a greater percentage of highly allergenic taxa found within the city, including Betula pendula that is not part of the local flora. This shows that through urban planting, the public and municipalities can unconsciously create a high risk for allergy sufferers. Daily average pollen counts from the six most frequently recorded pollen types were entered into Spearman’s correlation analysis with meteorological data. Mean daily temperature, relative humidity, daily rainfall and wind speed were found to significantly (p < 0.05) affect atmospheric pollen concentrations, but the relationships between pollen concentrations and meteorological variables can vary and so there is a need for more local studies of this nature.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land; 6. Clean water